Atypical role of sprouty in p21 dependent inhibition of cell proliferation in colorectal cancer - Zhang, Qiong (Mol Carcinog, 2015)
Sprouty (SPRY) appears to act as a tumor suppressor in cancer, whereas we reported that SPRY2 functions as a putative oncogene in colorectal cancer (CRC) [Oncogene, 2010, 29: 5241–5253]. In general, various studies established inhibition of cell proliferation by SPRY in cancer. The mechanisms by which SPRY regulates cell proliferation in CRC are investigated. We demonstrate, for the first time, suppression of SPRY2 augmented EGF‐dependent oncogenic signaling, however, surprisingly decreased cell proliferation in colon cancer cells. Our data suggest that cell cycle inhibitor p21(WAF1/CIP1) transcriptional activity being regulated by SPRY2. Indeed, suppression of SPRY2 significantly increased p21(WAF1/CIP1) mRNA and protein expression as well as p21(WAF1/CIP1) promoter activity. Conversely, overexpressing SPRY2 triggered a decrease in p21(WAF1/CIP1) promoter activity. Concurrent down‐regulation of both SPRY1 and SPRY2 also increased p21(WAF1/CIP1) expression in colon cancer cells. Increased nuclear localization of p21(WAF1/CIP1) in SPRY2 downregulated colon cancer cells may explain the inhibition of cell proliferation in colon cancer cells. Underscoring the biological relevance of these findings in SPRY1 and SPRY2 mutant mouse, recombination of floxed SPRY1 and SPRY2 alleles in mouse embryonic fibroblasts (MEFs) resulted in increased expression and nuclear localization of p21(WAF1/CIP1) and decreased cell proliferation. In CRC, the relationship of SPRY with p21 may provide unique strategies for cancer prevention and treatment. © 2015 The Authors. Molecular Carcinogenesis published by Wiley Periodicals, Inc.